Proposed five (5) new standard of procedures (SOP) for KAED announcement - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2018)
The ICT unit of KAED has prepared and tabled New Standard of Procedures (SOP)in Kulliyyah meeting to improve visibility of the Kulliyyah's events and programmes, and enhance ICT service efficiency to the customers.